2012
DOI: 10.1080/02755947.2012.686005
|View full text |Cite
|
Sign up to set email alerts
|

Female Length and Mass Quantify the Difference between Atlantic Salmon Ova Fecundity and Ova Deposition

Abstract: The population status of salmonids is often assessed as ova deposition relative to “ova conservation densities.” Traditional approaches to assessing ova deposition predict log(ova numbers) from log(female length) for Atlantic salmon Salmo salar based on calibrations for unspawned females. Better ova deposition predictions are obtained by using both female length and female mass, especially when part‐spawned females arrive at or leave local study sites, which are crucial to parameterizing such relationships. Im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…As the North Esk River is the key monitored river for Scottish S. salar, the implications will be appreciable irrespective of the outcome. In any such co-ordinated future study of ova production (not reliant on historical data) it would be desirable to record both body length and body mass per female (Bacon et al, 2012). Furthermore, measuring the sizes (diameters) of a sample of some 30 individual ova per female might elucidate the currently poorly predicted (only 31% of variance) average ovum volume per female.…”
Section: F U T U R E W O R Kmentioning
confidence: 99%
“…As the North Esk River is the key monitored river for Scottish S. salar, the implications will be appreciable irrespective of the outcome. In any such co-ordinated future study of ova production (not reliant on historical data) it would be desirable to record both body length and body mass per female (Bacon et al, 2012). Furthermore, measuring the sizes (diameters) of a sample of some 30 individual ova per female might elucidate the currently poorly predicted (only 31% of variance) average ovum volume per female.…”
Section: F U T U R E W O R Kmentioning
confidence: 99%
“…However, there were no significant trends in the length–weight relationships over this shorter time period (unpublished data), and Bacon et al. () showed that this relationship was constant for early running upland fish between two datasets collected 40 years apart. Despite the limited additional effect of declining spawner size on egg deposition, accounting for long‐term trends in size will improve estimates of egg deposition.…”
mentioning
confidence: 94%
“…It is therefore possible that the current analysis underestimates the effects of size if reductions in fish weight have exceeded those in length; that is, if the fecunditylength relationship has not been constant. However, there were no significant trends in the length-weight relationships over this shorter time period (unpublished data), and Bacon et al (2012) showed that this relationship was constant for early running upland fish between two datasets collected 40 years apart. Despite the limited additional effect of declining spawner size on egg deposition, accounting for long-term trends in size will improve estimates of egg deposition.…”
mentioning
confidence: 96%
See 2 more Smart Citations